Subversive scribes and the Solomonic narrative a rereading of 1 Kings 1-11 - Seibert, Eric A. 1969- (New York [u.a.] T & T Clark, 2006)
Propaganda, subversion, and Scripture -- Scribes and scribal subversion -- Prolegomena to reading 1 Kings 1-11 -- Propaganda and subversion in Solomon's rise to power: 1 Kings 1-2 -- Selected examples of subversion in 1 Kings 3-11
Includes bibliographical references and index
Teilw. zugl. Diss. 2002
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc; Bible -- O.T. -- Kings, 1st, I-XI. -- Criticism, interpretation, etc; Subversive activities -- Biblical teaching; Propaganda -- Biblical teaching; Scribes, Jewish; Subversive activities -- Biblical teaching; Propaganda -- Biblical teaching; Hochschulschrift